2020
DOI: 10.3390/cryst10020122
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and Structural Coloured Composite Films from Cellulose Nanocrystals/Hydroxypropyl Cellulose Lyotropic Suspensions

Abstract: Lyotropic colloidal aqueous suspensions of cellulose nanocrystals (CNCs) can, after solvent evaporation, retain their chiral nematic arrangement. As water is removed the pitch value of the suspension decreases and structural colour-generating films, which are mechanically brittle in nature, can be obtained. Increasing their flexibility while keeping the chiral nematic structure and biocompatible nature is a challenging task. However, if achievable, this will promote their use in new and interesting application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…%, from 95–97%, Sigma-Aldrich, MO, USA, p.a.) and an acid solution/solid ratio of 8:1 from adaptations of the acid hydrolysis method described elsewhere [ 57 , 58 ]. The reactional process occurred at 55 °C, under mechanical stirring, and the mixture was quenched with ultrapure water after 75 min of reaction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…%, from 95–97%, Sigma-Aldrich, MO, USA, p.a.) and an acid solution/solid ratio of 8:1 from adaptations of the acid hydrolysis method described elsewhere [ 57 , 58 ]. The reactional process occurred at 55 °C, under mechanical stirring, and the mixture was quenched with ultrapure water after 75 min of reaction.…”
Section: Methodsmentioning
confidence: 99%
“…The droplets were allowed to dry at 60 °C until they were a constant weight and samples were kept in a desiccator until further use. Moreover, 4 × 4 µm 2 height images were used to measure the average length of individual nanoparticles, as described by Saraiva et al (2020) [ 58 ]. The width of each particle used in the length determination was returned from the height profile along its length, as described by Honoratos-Rios et al (2018) [ 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, several strategies have been proposed to mitigate their intrinsically poor mechanical resistance. Such strategies usually involve the co-assembly with a plasticizer that does not compromise the self-assembly of the CNCs, such as surfactants [387], a neutral or anionic polymer [388][389][390], globular proteins [391], resins or sol-gel precursors [392,393]. Two recent examples from Walters et al [389] and from Saraiva et al [390] showed that a common cellulose derivative, hydroxypropyl cellulose (HPC), can be successfully used as a plasticizer for CNC photonic films, significantly preventing crack growth upon bending with respect to plain CNC films (Fig.…”
Section: Optical Functional Materialsmentioning
confidence: 99%
“…Despite its widespread use and seminal photonic studies in the 1970s and 1980s, the development of HPC‐based photonic applications has been slow. [ 7–13 ] Recently however, a growing interest in sustainable raw materials and their application has seen a shift in photonic HPC research toward practical applications [ 14–22 ] and large‐area processing. [ 17,18 ]…”
Section: Introductionmentioning
confidence: 99%